Settler Colonial Saskatchewan and Gender-based Violence Against Indigenous Women - Grafton, Emily; Fletcher, Amber (Journal of Critical Race Inquiry)

(untitled) (Queen's University, 2025)
Women and gender non-conforming people living in Saskatchewan, Canada, face staggeringly high rates of gender-based violence (GBV). These rates are disproportionately experienced by Indigenous women, girls, and Two-Spirit or gender-queer individuals, which can be attributed to both historical and ongoing settler-colonial practices. This timely article provides a structural analysis linking GBV against women and gender non-conforming people to the province's settler colonial politics. It does so by applying a feminist intersectional research methodology to a literature review of legislation, policy, provincial budgets, peer-reviewed scholarship, industry-related reports, and media documents. As such, this article argues that GBV perpetrated against Indigenous women is central to settler colonial violence, enabling the settler state to foster settler colonial expansion and Indigenous dispossession, which are power imbalances in urgent need of redistribution. These settler colonial mechanics are readily observable in Saskatchewan, a province at the forefront of settler colonial development in Canada, partly through these staggering and disproportionate GBV rates.